Length–weight relationships of six tropical fish species from Chilika Lagoon, India. (2nd September 2016) - Panda, D.; Karna, S. K.; Mukherjee, M.; Manna, R. K.; Suresh, V. R.; Sharma, A. P.
Summary: The length weight relationships (LWRs) of six tropical fish species from Chilika Lagoon, India were studied. Specimens were caught using a wide range of fishing gear operated in the lagoon from January to December 2014. The fresh specimens were measured for total length and weight, then dissected and the sex confirmed. Previously unavailable in FishBase, the detailed LWRs of Daysciaena albida, Eleutheronema tetradactylum, Etroplus suratensis and Mystus gulio are reported for the first time. Maximum total lengths reported for Nematalosa nasus and Osteogeneiosus militaris in this study are new records for these species. The existence of a differential growth between male and female O. militaris was confirmed, which was not known earlier.